WŁASNOŚĆ I INTERESY. PRYWATYZACJA W POLSCE W UJĘCIU SOCJOLOGII GOSPODARKI - Tittenbrun, Jacek (Wydział Prawa i Administracji UAM, 1999)
The Author focuses on sociological contents of privatisation processes in enterprises with special respect to their implications for social condition of main social groups (classes) participating in these processes. The analysis of these economic and social problems is referred to the theory of property (first of all - of stocks’ property. Then discussing different ways of enterprises’ privatisation the Author indicates certain negative effects - as for instance realising extraordinary gains by owners of companies after having artificially reduced the price of evaluated means of production as taken over from privatised enterprises. The Author describes also material condition of the employees in newly created companies, their influence on management, property relationship in such a firm as well as, finally, opinions of the employees on their new situation: so, these employees are, in the same time, joint owners of a firm.
PROPERTY AND INTERESTS. PRIVATISATION IN POLAND AS FORMULATED IN TERMS OF SOCIOLOGY OF ECONOMY